Decentralisation without Autonomy: Elite Capture and the Political Economy of Local Governance in Nigeria - Abubakar, Sulaiman S (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2026)
Decentralisation has been widely promoted as a mechanism for enhancing democratic governance, accountability, and service delivery, particularly in developing countries. In Nigeria, however, the formal adoption of decentralised structures has not translated into meaningful local government autonomy, raising important questions about the political realities underpinning governance reforms. Although existing scholarship has generated important insights into decentralisation, local government autonomy, fiscal arrangements, governance performance, and elite capture, comparatively less attention has been given to explaining how the political and institutional mechanisms through which elite actors constrain local autonomy shape governance outcomes within decentralised systems. This study examines the paradox of decentralisation without autonomy by investigating how, and through what political and institutional mechanisms, federal- and state-level elites constrain local government autonomy in Nigeria, and with what implications for governance and citizen engagement. Adopting a political economy perspective, the study draws on secondary data from constitutional provisions, policy documents, audit reports, and empirical studies, which are analysed using qualitative content and thematic analysis. The findings show that fiscal centralisation, administrative interference, and patronage networks constitute the principal mechanisms through which local autonomy is constrained. While state governments are the primary actors through which these mechanisms operate, federal institutions also sustain the broader constitutional and intergovernmental framework that enables them. Consequently, local governments function less as autonomous centres of governance than as dependent institutions operating within a hierarchical political system. The study contributes to decentralisation, political economy, and public administration scholarship by advancing a mechanism-based explanation of how formal decentralisation can coexist with enduring patterns of elite control, thereby informing ongoing debates on decentralisation reform in Nigeria and comparable contexts.